Assessing the reactivity of the N, N′‐diamidocarbenes toward compounds containing early p‐block elements1. (18th November 2014) - Lastovickova, Dominika N.; Moerdyk, Jonathan P.; Kelley, Andrea R.; Bielawski, Christopher W.; Moss, R. A.; Gudmundsdottir, A.
<x xml:space="preserve">Abstract</x> The ability of an isolable N, N′‐diamidocarbene (DAC) to activate compounds containing early p‐block elements was explored. At ambient temperature, the DAC formally inserted into the Si–H bonds of various silanes to afford the corresponding DAC–silane adducts. The aforementioned adducts did not undergo intramolecularring expansion as observed with other carbene–silane analogues. The DAC was also found to form a coordination complex with aluminum chloride, and a structurally rich, tris(aluminum) species was obtained upon exposure of the DAC to trimethylaluminum. The results gleaned from these studies are expected to facilitate the development of novel organometallic species as well as of new types of organocatalyzed silylations and aluminations. Copyright © 2014 John Wiley & Sons, Ltd.